2012
DOI: 10.1002/marc.201100641
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Block Copolymers by Combination of Atom Transfer Radical Polymerization and Visible Light‐Induced Free Radical Promoted Cationic Polymerization

Abstract: A new synthetic approach for the preparation of block copolymers by mechanistic transformation from atom transfer radical polymerization (ATRP) to visible light-induced free radical promoted cationic polymerization is described. A series of halide end-functionalized polystyrenes with different molecular weights synthesized by ATRP were utilized as macro-coinitiators in dimanganese decacarbonyl [Mn(2) (CO)(10) ] mediated free radical promoted cationic photopolymerization of cyclohexene oxide or isobutyl vinyl e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…We have previously shown that manganese based radical generation process can successfully be employed in different modes of polymerization processes including radical promoted cationic polymerization (51), mechanistic transformation (52,53), radical coupling (54), hyper-branching (55) and grafting from polyolefines (56). Recent studies from our laboratory showed that this chemistry can be used as a photoredox catalyst system for the ATRP of vinyl monomers such as methyl methacrylate, methyl acrylate and styrene (57).…”
Section: Visible Light-induced Atrp By Using Dimanganese Decacarbonylmentioning
confidence: 96%
“…We have previously shown that manganese based radical generation process can successfully be employed in different modes of polymerization processes including radical promoted cationic polymerization (51), mechanistic transformation (52,53), radical coupling (54), hyper-branching (55) and grafting from polyolefines (56). Recent studies from our laboratory showed that this chemistry can be used as a photoredox catalyst system for the ATRP of vinyl monomers such as methyl methacrylate, methyl acrylate and styrene (57).…”
Section: Visible Light-induced Atrp By Using Dimanganese Decacarbonylmentioning
confidence: 96%
“…These polymeric cations were able to initiate the cationic polymerization of both cyclohexene oxide and isobutyl vinyl ether to yield essentially block copolymers containing mechanistically incompatible segments. 90 More recently, Yagci and coworkers 91 demonstrated that an iodo functionalized polyethylene (PE-I), synthesized by the addition of iodine after catalyzed polyethylene chain growth on magnesium, was also an efficient macroinitiator for thermally induced, controlled free radical polymerization of MMA mediated by Mn 2 (CO) 10 that led to the synthesis of original PE-based block copolymers. Although the photochemical method failed to produce any block copolymer due to the insolubility of the precursor PE, the thermal treatment not only enables the dissolution of PE-I macroinitiator but also activates Mn 2 (CO) 10 which can further participate in block copolymerization according to the reactions described for the photochemical process (Scheme 9).…”
Section: Block and Graft Copolymersmentioning
confidence: 99%
“…One of the literature criteria used to define a controlled polymerization is based on the Ɖ values, where M w /M n ≤ 1.5 is considered a narrow molecular weight distribution [4,[34][35][36] . Normally, very narrow Ɖ values (M w /M n ≤ 1.2) are obtained at low monomer conversion rates and/or by using solvent in the polymerization [25,37,38] . In the present work, we conducted the PS polymerization in bulk resulting Ɖ values slightly above very narrow Ɖ values (M w /M n ≤ 1.2) but still in the range of CRP Ɖ values (M w /M n ≤ 1.5).Thus, this work is in agreement with literature reported Ɖ values [4,6,[20][21][22]25,35] .…”
Section: H Nmr (M Nmrmentioning
confidence: 99%